The reference book - Hawthorne, John (John P.); Manley, David (David Jeffrey) (Oxford : Oxford University Press, 2012)
How do language and thought connect to things in the world? John Hawthorne and David Manley offer an original and ambitious treatment of the semantic phenomenon of reference and the cognitive phenomenon of singular thought, leading to a new unified account of definite and indefinite descriptions, names and demonstratives.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Reference (Philosophy); Reference (Linguistics)